THE BENEFITS OF NON-BIOLOGICAL THERAPY IN CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD) - Anindita, Adinda Chika (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction –  Autism Spectrum Disorders (ASD) are a group of neurodevelopmental disorders characterized by three main problems, namely the presence of communication disorders, impaired reciprocal social interaction with the surrounding environment, and restricted, repetitive, and stereotyped behavior patterns in the first 3 years of age. In Indonesia, there were around 112,000 ASD sufferers in 2012, while in 2015 it was estimated that 1 in 250 children had ASD, or around 134,000 people. Methods –  The author used the literature review method by collecting the results of several kinds of literature on ASD, and non-biological therapy and their benefits in ASD children. The literature on non-biological therapy and its benefits in ASD children is limited to 2011-2021. Results –  Autism is a lifelong disorder, so it is important to recognize it as early as possible, and parents need to understand the problem. It's important to remember that the cause of autism is unknown, and no single drug has been found that can cure ASD, but some therapies can suppress ASD symptoms that can help ASD lead a more productive life by reducing symptoms and improving skills. Discuss – There is no definitive therapy that can cure ASD, but therapy is aimed at improving ASD symptoms. Non-biological therapy which includes behavioral therapy (such as TEACCH or ABA) is currently used as first-line therapy for ASD. Conclusion –  Symptoms that appear in ASD children vary widely, therefore the therapy given is individual and depends on the circumstances and symptoms that appear. There are many types of non-biological therapies for ASD, such as ABA, TEACCH, PECS, Caregiver-mediated Intervention, Parent-mediated Communication, SIT, and AIT. These therapies have been shown to have benefits in improving ASD symptoms such as communication skills, social interaction, and behavior, where each therapy has different benefits in each type. These therapies are given to everyone as needed.   Keywords: non-biological, children, autism.